Immunotherapy for Cancer in Kidney Transplant Patients: A Difficult Balance Between Risks and Benefits - Mónica Bolufer; Mónica Bolufer; Jordi Soler; Jordi Soler; María Molina; María Molina; Omar Taco; Omar Taco; Anna Vila; Anna Vila; Manuel Macía; Manuel Macía (Transplant International, 2024)
Cancer is a major cause of morbidity and mortality in kidney transplant patients. Unfortunately, the use of new anti-cancer therapies such as immune checkpoint inhibitors (ICPIs) in this population has been associated with rejection rates up to 40%, in retrospective studies. The main challenge is to maintain the patient in a delicate immunologic balance in which, while antitumor therapy defeats cancer the graft is safely protected from rejection. Recent clinical trials with ICPI have included kidney transplant recipients (KTRs) and the results advocate for a paradigm shift in the management of basal immunosuppression. This suggests that downward adjustments should be avoided or, even better, that this adjustment should be “dynamic.” This review summarizes the latest scientific evidence available in renal transplantation under ICPI treatment: case series, prospective studies, histopathologic diagnosis, immunosuppression regimens and new biomarkers. This article will provide the latest information in on this specific field, allowing nephrologists to gain valuable knowledge and to be aware of new approaches to immunosuppression management in oncological kidney transplant patients.